2017
DOI: 10.1253/circj.cj-16-1089
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendage Thrombi Formation in Japanese Non-Valvular Atrial Fibrillation Patients During Anticoagulation Therapy ― Warfarin vs. Direct Oral Anticoagulants ―

Abstract: Background: Atrial fibrillation (AF) is a common cardiac arrhythmia, associated with increased cardiovascular morbidity and mortality including thromboembolic events. The aims of this study were to assess the prevalence of left atrial appendage (LAA) thrombi in Japanese non-valvular atrial fibrillation (NVAF) patients undergoing preprocedural transesophageal echocardiography (TEE) during anticoagulation therapy, and to compare the efficacy of warfarin and direct oral anticoagulants (DOAC). Methods and Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 22 publications
4
46
0
4
Order By: Relevance
“…None of the patients in this study taking a NOAC had LA/LAA thrombus; their demographics were comparable to the rest of the population, and the CHA 2 DS 2 VASc scores ranged from 0 to 5, similar to the population on warfarin. This finding is consistent with other studies that have shown that the incidence of thrombus in patients undergoing pre-ablation TOE is either similar (21) or less (22) than those patients on warfarin.…”
Section: Discussionsupporting
confidence: 92%
“…None of the patients in this study taking a NOAC had LA/LAA thrombus; their demographics were comparable to the rest of the population, and the CHA 2 DS 2 VASc scores ranged from 0 to 5, similar to the population on warfarin. This finding is consistent with other studies that have shown that the incidence of thrombus in patients undergoing pre-ablation TOE is either similar (21) or less (22) than those patients on warfarin.…”
Section: Discussionsupporting
confidence: 92%
“…(C) Real‐world studies results concerning dose adjustments of apixaban. (D) Results from direct oral anticoagulants overall adjustments regarding dose appropriateness…”
Section: Resultsmentioning
confidence: 99%
“…Canadian study, 44 where a total of 47 patients were included, among (D) Results from direct oral anticoagulants overall adjustments regarding dose appropriateness 5,9,11,25,27,28,32,34,37,39,40,42,44,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] whom 25 (53%) were receiving apixaban inconsistent with the ARIS-TOTLE trial and the product monograph.…”
Section: Study and Also By A Smallmentioning
confidence: 99%
“…Furthermore, in a study of AF patients being treated with either a vitamin-K antagonist (warfarin) or a non-vitamin K antagonist oral anticoagulation (NOAC) drug, 2.7% had a LAA thrombus seen on transesophageal echocardiogram (TEE) despite compliance with anticoagulation. 54 Those with thrombus had a mean LA diameter of 47 mm compared with 41 mm in those without thrombus ( P = 0.003). 55 …”
Section: Prediction Of Stroke Risk Based On Structural and Functionalmentioning
confidence: 91%
“…54 Those with thrombus had a mean LA diameter of 47 mm compared with 41 mm in those without thrombus ( P = 0.003). 55 …”
Section: Prediction Of Stroke Risk Based On Structural and Functionalmentioning
confidence: 91%